2019
DOI: 10.1542/peds.2018-1565
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin for Staphylococcus aureus Decolonization of Infants in Neonatal Intensive Care Units

Abstract: BACKGROUND AND OBJECTIVES: Staphylococcus aureus (SA) is the second leading cause of lateonset sepsis among infants in the NICU. Because colonization of nasal mucosa and/or skin frequently precedes invasive infection, decolonization strategies, such as mupirocin application, have been attempted to prevent clinical infection, but data supporting this approach in infants are limited. We conducted a phase 2 multicenter, open-label, randomized trial to assess the safety and efficacy of intranasal plus topical mupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…28,29 Some prospective data show success with routine surveillance of new admissions followed by decolonization with nasal mupirocin to reduce invasive disease. 30 Whether environmental contamination contributes to S. aureus acquisition in the NICU remains unclear. No data exist, in any age group, to suggest that environmental culturing provides useful information to prevent S. aureus transmission and infections.…”
Section: Questionmentioning
confidence: 99%
See 3 more Smart Citations
“…28,29 Some prospective data show success with routine surveillance of new admissions followed by decolonization with nasal mupirocin to reduce invasive disease. 30 Whether environmental contamination contributes to S. aureus acquisition in the NICU remains unclear. No data exist, in any age group, to suggest that environmental culturing provides useful information to prevent S. aureus transmission and infections.…”
Section: Questionmentioning
confidence: 99%
“…2,21,[32][33][34] Infants colonized with MSSA are also at increased risk of infection. 30,31 In some populations, eradicating S. aureus colonization, via decolonization, can reduce the risk of infection. 21,28,30,35 Both targeted and universal decolonization strategies have been employed in NICUs, but data are more limited for universal decolonization.…”
Section: Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, oral mupirocin is rapidly metabolised, thus lowering the risk of causing adverse effects in the nursing baby 17. A clinical trial showed that mupirocin was generally well tolerated in infants 23…”
Section: Introductionmentioning
confidence: 99%